Surface-Modifying Effect of Zwitterionic Polyurethane Oligomers Complexed with Metal Ions on Blood Compatibility - Ga, Dong-Heon; Lim, Chung-Man; Jang, Yoonsun; Son, Tae Il; Han, Dong Keun; Joung, Yoon Ki (한국조직공학과 재생의학회, 2022)
Background To prevent unsolved problems of medical devices, we hypothesized that combinatorial effects of zwitterionic functional group and anti-bacterial metal ions can reduce effectively the thrombosis and bacterial infection of polymeric biomaterials. In this research, we designed a novel series of zwitterionic polyurethane (zPU) additives to impart anti-thrombotic properties to a polyvinyl chloride (PVC) matrix. Methods We have synthesized zPUs by combination of various components and zPUs complexed with metal ions. Zwitterion group was prepared by reaction with 1,3-propane sultone and Nmethyldiethanolamine and metal ions were incorporated into sulfobetaine chains via molecular complexation. These zPU additives were characterized using FT-IR, 1H-NMR, elemental analysis, and thermal analysis. The PVC film blended with zPU additives were prepared by utilizing a solvent casting and hot melting process. Results Water contact angle demonstrated that the introduction of zwitterion group has improved hydrophilicity of polyurethanes dramatically. Protein adsorption test resulted in improved anti-fouling effects dependent on additive concentration and decreases in their effects by metal complexation. Platelet adhesion test revealed anti-fouling effects by additive blending but not significant as compared to protein resistance results. Conclusion With further studies, the synthesized zPUs and zPUs complexed with metal ions are expected to be used as good biomaterials in biomedical fields. Based on our results, we can carefully estimate that the enhanced anti-fouling effect contributed to reduced platelet adhesion. Graphic Abstract Schematic explanation of the effect of zwitterionic polyurethane additives for blood-compatible and anti-bacterial bulk modification.